Influence of the modulation doping to the mobility of two-dimensional electron gases in Si/SiGe - Werner, J.; Oehme, Michael; Kasper, E.; Schulze, J. (Thin Solid Films, 2010)
The influence of the doping densities to the low temperature mobility of 2DEG in Si/SiGe is investigated. The SiGe modulation doped quantum well structures are realized by the method of molecular beam epitaxy (MBE). Different concepts for the needed virtual substrate are implemented to assess the influence from the quality of the samples to the mobility behavior. The modulation doping is varied between 6 * 1013/cm2 and 3 * 1012/cm2. In contrast to the theory of remote Coulomb scattering, it is observed that the low temperature mobility of two-dimensional electron gas in Si-channels increases with higher doping density. © 2009 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: 2DEG; Electron Gas; Electron mobility; Modulationdoping; Strained Si